Interactive versus Collaborative Writing Instruction: An Experimental Study - Ali Taghinezhad; Mohammad Ali Ayatollahi; Mahboobeh Azadikhah (Journal of Modern Research in English Language Studies)
This study investigated the effects of Interactive and Collaborative Instructional pedagogies on Iranian EFL learners' writing. It adopted pre-test and post-test control group quasi-experimental design with two experimental and one control groups. The participants were 90 college students in two branches of Islamic Azad University. The main data collection tool was an essay writing task. Data were analyzed using ANCOVA. Pre-test post-test comparisons revealed that students who received interactive pedagogy gained the most from the instruction t= -18.302; p = 0.000; p< 0.5, followed by students who received collaborative pedagogy with a significance level of t= -16.253; p = 0.000; p < 0.5. The control group recorded no significant gain in their post-test performance t= 0.339; p = 0.736; p> 0.5. The total variance accounted for by all the independent variables taken together was 51% (i.e. W2 = 0.51%). Findings indicated that interactive pedagogies befitted students more than collaborative ones.